Politik Keamanan Jagoan Madura - Ardhie Raditya (Jurnal Studi Pemerintahan, 2011)
This research explains the local strongmen in Madura, named Blater. The power was not only obtained through mastering either economic capital or structural power but through the power can be obtained through managing people security. This research uses descriptive-qualitative method for explaining the result of this research. The result of this research shows that the democracy has been used as an opportunity to reach the power conducted by local strongman in Madura. They were extremely intelligent in creating public fear as a power commodity that was used for political interest, particularly in the election of regional heads. They have established structural-functional relationships indirectly between bureaucrats and security apparatus. With courage and respect values, the Blaters use people’s fears as a bridge to compose security politics in the era of democracy.